EFFECTIVENESS OF VIDEO SMARTPHONE-BASED TUTORIALS TO INCREASED KNOWLEDGE AND FAMILY ATTITUDE IN MAINTAINING THE ACTIVITY DAILY LIVING (ADL) SCHIZOPHRENIC PATIENTS - Irfan Irfan (Stikes Graha Edukasi Makassar, 2019)
Objektive: Activity Daily Living (ADL) is the most common issue with schizophrenic patients. Schizophrenic patients need help and support from families in the fulfillment of Activities Daily Living (ADL). Providing health education to the family can increase family knowledge in the treatment process. Use of video-based media tutorials that can provide health education information through animation video demonstrations. Method: This research uses quasi experimental research method with pretest and posttest with control group approach. The research sample was 40 people of 341 members of the Schizophrenia family, who were recruited through purposive sampling and divided into 2 groups, 20 respondents in intervention group and 20 respondents control group. The knowledge of respondents was measured using instruments developed by researchers and conducted test content and construct test with the value of Cronbach's Alpha 0.954. Data analyzed using T-Test. Results : There is no meaningful difference among intervention Group (IG) and Control Group (CG). Video smartphone-based tutorial of knowledge (IG=0,000, CG=0,000 ) and family attitude (IG=0,000, CG=0,000 in maintaining the activity daily living (ADL) disorder patient. Conclusion: The conclusion of this study that the administration of health education intervention using audiovisual media video smartphone-based tutorials showed significant influence on the increased knowledge and family attitude about Activities Daily Living (ADL) in schizophrenic patients even though statistically control group get same results.